Impacts of environmental factors on the climbing behaviors of herbaceous stem‐twiners. Issue 22 (8th October 2017) - Hu, Liang; Chen, Youfang; Liu, Meicun
Abstract: The curvature of the helical trajectory formed by herbaceous stem‐twiners has been hypothesized to be constant on uniformly sized cylindrical supports and remains constant on different supports varying in diameter. However, experimental studies on the constant curvature hypothesis have been very limited. Here, we tested the hypothesis in a series of experiments on five herbaceous stem‐twiners ( Ipomoea triloba, Ipomoea nil, Phaseolus vulgaris, Vigna unguiculata, and Mikania micrantha ). We investigated how internode characteristics (curvature [β], diameter [ d ], and length [ L ]) and success rate (SR) of twining shoots would be affected by support thickness ( D ), temperature ( T ), illumination, and support inclination. The results showed that: (1) the SR of tested species decreased, but d increased with increasing support thickness. The β of the twining shoots on erect cylindrical poles was not constant, but it decreased with increasing d or support thickness. (2) The SR of tested species was not obviously reduced under low‐temperature conditions, but their β was significantly higher and d significantly lower when temperature was more than 5°C lower. (3) The SR, d, and L of two tested Ipomoea species significantly declined, but β increased under 50% shading stress. (4) The curvatures of upper semicycles of I. triloba shoots on 45° inclined supports were not significantly different from curvatures of those shoots climb on erect supports, whereas the curvatures of lower semicycles were 40%–72% higher than curvatures of upper semicycles. Synthesis : Our study illustrates that stem curvatures of a certain herbaceous stem‐twiners are not constant, but rather vary in response to external support, temperature, and illumination conditions. We speculate that herbaceous stem‐twiners positively adapt to wide‐diameter supports by thickening their stems and by reducing their twining curvatures. This insight helps us better understand climbing processes and dynamics of stem‐twiners in forest communities and ecosystems. Abstract : Our finding rejected the well‐accepted constant curvature hypothesis and revealed that the climbing characteristics and ascending efficiency of stem‐twiners varies with the changes in external support or environmental factors. Our study shed light on the key process during the vegetative spread of herbaceous stem‐twiners.